Organic fiber AGM separator and application thereof
By using nitrogen-doped reducing slurry of graphene oxide/lead oxide composite in the AGM separator, the problems of susceptibility to puncture and hydrophobicity of traditional AGM separators are solved, achieving higher penetration dendrites and longer battery life.
Patent Information
- Application Number
- CN202510102175.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Traditional AGM separators are easily short-circuited by lead sulfate dendrites during the charging and discharging of the battery, and the fibers are hydrophobic, which increases the gaps and forms an open oxygen conforming to the channel, affecting the performance and life of the battery.
The slurry of high alkali glass wool, medium alkali glass fiber, two-component polyester fiber and nitrogen-doped reducing graphene oxide/lead oxide composite material is coated on the AGM separator substrate and is acid-impregnated and cured to form an organic fiber AGM separator.
It improves the penetration dendritic thorn resistance of AGM partitions, extends the service life of the battery, and improves the mechanical properties and corrosion resistance of the partitions by enhancing the specific surface area and chemical stability of the composite material.
Smart Images

Figure BDA0005254472000000091
Abstract
Description
Technical Field
[0001] The invention belongs to the field of storage batteries, and in particular relates to an organic fiber AGM separator and application thereof. Background Art
[0002] AGM separators are composed of chemical grade borosilicate glass fibers, which are 1 to 2 mm long and of varying thickness (0.1 to 10 μm in diameter). The ratio of different fibers determines the balance between the different functions of the separator and the price of the separator. These fibers are hydrophilic and absorb electrolyte. The finer fibers in the separator (i.e., fibers with smaller diameters) have a larger surface area and form smaller micropores with smaller inner diameters, but are more expensive. AGM separators also contain 15% to 18% of polymer fibers such as PP and PE, which increase the mechanical strength of the separator, promote the formation of gas channels, and also reduce the price of the separator.
[0003] Traditional high-specific surface area AGM separators, although fine in fiber and good in acid absorption, often lack mechanical strength, and are easily punctured and short-circuited by lead sulfate dendrites during battery charging and discharging. At the same time, organic fibers are hydrophobic, which increases the gaps in the AGM separators and forms open oxygen channels. After oxygen is precipitated from the positive plate, it is transmitted to the negative plate, and then a reduction reaction occurs on the negative plate, which alleviates the problem of battery cell lagging behind to a certain extent. At the same time, organic fibers improve the compressive resistance of the separators, slow down the shedding of active substances, and increase the battery cycle life.
[0004] Patent applications with publication numbers CN103855346A and CN104201319A mainly improve the performance of the AGM separator by adding silicon dioxide to improve the composition of the fibers in the separator. Further research shows that the above AGM separator still has the following technical problems: the separator has a small specific surface area, low wet elasticity, and the battery capacity decays quickly; in addition, due to the large pore size on the glass fiber separator, the prevention performance of short circuit caused by lead dendrite puncture needs to be further improved, otherwise it will still affect the service life of the battery. Summary of the invention
[0005] The object of the present invention is to provide an organic fiber AGM separator and its application to solve the problem of poor resistance to dendrite puncture of battery separator.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An organic fiber AGM separator, comprising high-alkali glass wool, medium-alkali glass fiber, bicomponent polyester fiber and a slurry containing a nitrogen-doped reduced graphene oxide / lead oxide composite material;
[0008] The nitrogen-doped reduced graphene oxide / lead oxide composite material is prepared by the following steps:
[0009] Graphene oxide, deionized water and anhydrous ethanol are uniformly dispersed by ultrasonic method, aniline is slowly dropped into the mixture, and ultrasonic stirring is performed to obtain a mixed solution; lead acetate powder is added into the mixed solution, ultrasonic stirring is performed, hydrothermal reaction is performed, washing is performed, freeze drying is performed, and pyrolysis is performed in a rare gas atmosphere to obtain a nitrogen-doped reduced graphene oxide / lead oxide composite material.
[0010] Furthermore, the usage ratio of the graphene oxide, deionized water, anhydrous ethanol, aniline and lead acetate is (20-30) mg: (10-20) mL: (10-20) mL: (0.1-0.4) mL: (150-200) mg.
[0011] Furthermore, the ultrasonic time is 20-30 minutes; the stirring time is 0.5-1 hour.
[0012] Furthermore, the hydrothermal reaction is carried out at 180-200° C. for 20-24 hours.
[0013] Furthermore, the pyrolysis is performed by heating to 450-500°C at a rate of 5-10°C / min and pyrolysis for 1-2h.
[0014] A method for preparing an organic fiber AGM separator comprises the following steps:
[0015] S1. High-alkali glass wool, medium-alkali glass fiber, and two-component polyester fiber are mixed in proportion to prepare a slurry, and then an AGM separator matrix is prepared according to an AGM separator preparation process;
[0016] S2. Evenly mix the nitrogen-doped reduced graphene oxide / lead oxide composite material, boric acid, lead oxide powder, barium sulfate, humic acid, sodium lignin sulfonate, short fibers, acetylene black, deionized water and dilute sulfuric acid to obtain a slurry containing the nitrogen-doped reduced graphene oxide / lead oxide composite material, apply the slurry on an AGM separator substrate, immerse it in a dilute sulfuric acid solution, and solidify it to obtain an organic fiber AGM separator.
[0017] Furthermore, the dosage ratio of the nitrogen-doped reduced graphene oxide / lead oxide composite material, boric acid, lead oxide powder, barium sulfate, humic acid, sodium lignin sulfonate, short fibers, acetylene black, deionized water and dilute sulfuric acid is (20-40) mg: (5-10) mg: (4-6) g: (30-40) mg: (15-25) mg: (15-25) mg: (2-4) mg: (6-10) mg: (1-2) mL: (0.5-1) mL.
[0018] Furthermore, the mass fraction of the dilute sulfuric acid solution is 20% to 30%.
[0019] Furthermore, the immersion time is 10-20s.
[0020] Furthermore, the curing conditions are: air humidity 90% to 95%, room temperature 60-80° C., and curing for 20-24 hours.
[0021] Furthermore, the organic fiber AGM separator is used in batteries.
[0022] Beneficial effects of the present invention:
[0023] (1) The organic fiber AGM separator provided by the present invention is prepared by synthesizing a nitrogen-doped reduced graphene oxide / lead oxide composite material, preparing the composite material into a slurry, coating the slurry on an AGM separator substrate, and then acid-immersing and curing the slurry. The slurry has excellent resistance to dendrite punctures and prolongs the service life of the battery.
[0024] (2) The nitrogen-doped reduced graphene oxide / lead oxide composite material used in the present invention has a large specific surface area, which is beneficial to improving the performance of the battery. The nitrogen-doped reduced graphene oxide avoids the agglomeration of graphene oxide flakes and enhances the tightness of the composite material with negatively charged ions. The graphene oxide not only tightly combines with boric acid, thereby improving the dispersibility and stability of boron, but also provides abundant deposition sites for lead oxide. In addition, due to the chemical stability of the composite material itself, the mechanical properties and corrosion resistance of the separator are improved, which is also beneficial to improving the separator's resistance to dendrite thorns and improving the battery cycle life.
[0025] (3) The lead oxide used in the present invention can improve the conductivity of graphene oxide, while boric acid can improve the bonding force between the grid and the active material, thereby indirectly improving the conductivity and battery performance. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] This embodiment provides an organic fiber AGM separator and its application, which is prepared by the following steps:
[0029] S1. High-alkali glass wool, medium-alkali glass fiber, and two-component polyester fiber are mixed in proportion to prepare a slurry, and then an AGM separator matrix is prepared according to an AGM separator preparation process;
[0030] S2. Ultrasonically disperse 25 g of graphene oxide, 15 mL of deionized water and 15 mL of anhydrous ethanol, slowly drop 0.3 mL of aniline, ultrasonicate for 20 min, stir for 0.5 h, and obtain a mixed solution; add 175 mg of lead acetate powder to the mixed solution, ultrasonicate for 20 min, stir for 0.5 h, hydrothermally react at 180 ° C for 24 h, wash with anhydrous ethanol and deionized water alternately for 3 times, freeze-dry, heat to 450 ° C at a rate of 5 ° C / min in a rare gas atmosphere, and pyrolyze for 1.5 h to obtain a nitrogen-doped reduced graphene oxide / lead oxide composite material;
[0031] S3. Evenly mix 30 mg of nitrogen-doped reduced graphene oxide / lead oxide composite material, 8 mg of boric acid, 5 g of lead oxide powder, 40 mg of barium sulfate, 20 mg of humic acid, 20 mg of sodium lignin sulfonate, 3 mg of short fibers, 8 mg of acetylene black, 1.5 mL of deionized water and 1 mL of 30% by mass dilute sulfuric acid to obtain a slurry containing nitrogen-doped reduced graphene oxide / lead oxide composite material. Coat the slurry on the AGM separator substrate, immerse it in a dilute sulfuric acid solution for 15 seconds, and cure it at an air humidity of 95% and room temperature of 60°C for 24 hours to obtain an organic fiber AGM separator.
[0032] The prepared organic fiber AGM separator is applied to batteries.
[0033] Example 2
[0034] Compared with Example 1, this embodiment differs in that the raw material ratio in S3 is changed, and the specific implementation steps of S3 are:
[0035] S3. Evenly mix 40 mg of nitrogen-doped reduced graphene oxide / lead oxide composite material, 5 mg of boric acid, 4 g of lead oxide powder, 30 mg of barium sulfate, 25 mg of humic acid, 15 mg of sodium lignin sulfonate, 2 mg of short fibers, 10 mg of acetylene black, 2 mL of deionized water and 1 mL of 30% by mass dilute sulfuric acid to obtain a slurry containing nitrogen-doped reduced graphene oxide / lead oxide composite material. Coat the slurry on the AGM separator substrate, immerse it in a dilute sulfuric acid solution for 15 seconds, and cure it at an air humidity of 95% and room temperature of 60°C for 24 hours to obtain an organic fiber AGM separator.
[0036] The prepared organic fiber AGM separator is applied to batteries.
[0037] The remaining raw materials and preparation process remain the same as in Example 1.
[0038] Example 3
[0039] Compared with Example 1, the present embodiment is different in that the raw material ratio in S3 is changed again, and the specific implementation steps of S3 are:
[0040] S3. Evenly mix 20 mg of nitrogen-doped reduced graphene oxide / lead oxide composite material, 10 mg of boric acid, 6 g of lead oxide powder, 40 mg of barium sulfate, 15 mg of humic acid, 25 mg of sodium lignin sulfonate, 4 mg of short fibers, 6 mg of acetylene black, 1 mL of deionized water and 0.5 mL of 30% by mass dilute sulfuric acid to obtain a slurry containing nitrogen-doped reduced graphene oxide / lead oxide composite material. Coat the slurry on the AGM separator substrate, immerse it in a dilute sulfuric acid solution for 15 seconds, and cure it at an air humidity of 95% and room temperature of 60°C for 24 hours to obtain an organic fiber AGM separator.
[0041] The prepared organic fiber AGM separator is applied to batteries.
[0042] The remaining raw materials and preparation process remain the same as in Example 1.
[0043] Example 4
[0044] Compared with Example 1, the difference between this example and Example 1 is that "25 g of graphene oxide, 0.3 mL of aniline and 175 mg of lead acetate" in S2 is changed to "30 g of graphene oxide, 0.1 mL of aniline and 150 mg of lead acetate", and the specific implementation steps of S2 are:
[0045] S2. Ultrasonically disperse 30 g of graphene oxide, 15 mL of deionized water and 15 mL of anhydrous ethanol, slowly drop 0.1 mL of aniline, ultrasonicate for 20 min, stir for 0.5 h, and obtain a mixed solution; add 150 mg of lead acetate powder to the mixed solution, ultrasonicate for 20 min, stir for 0.5 h, hydrothermally react at 180 ° C for 24 h, wash with anhydrous ethanol and deionized water alternately for 3 times, freeze-dry, heat to 450 ° C at a rate of 5 ° C / min in a rare gas atmosphere, and pyrolyze for 1.5 h to obtain a nitrogen-doped reduced graphene oxide / lead oxide composite material;
[0046] The prepared organic fiber AGM separator is applied to batteries.
[0047] The remaining raw materials and preparation process remain the same as in Example 1.
[0048] Example 5
[0049] Compared with Example 1, the difference between this embodiment and Example 1 is that "25 g of graphene oxide, 0.3 mL of aniline and 175 mg of lead acetate" in S2 is changed to "20 g of graphene oxide, 0.4 mL of aniline and 200 mg of lead acetate", and the specific implementation steps of S2 are:
[0050] S2. Ultrasonically disperse 20 g of graphene oxide, 15 mL of deionized water and 15 mL of anhydrous ethanol, slowly drop 0.4 mL of aniline, ultrasonicate for 20 min, stir for 0.5 h, and obtain a mixed solution; add 200 mg of lead acetate powder to the mixed solution, ultrasonicate for 20 min, stir for 0.5 h, hydrothermally react at 180 ° C for 24 h, wash with anhydrous ethanol and deionized water alternately for 3 times, freeze-dry, heat to 450 ° C at a rate of 5 ° C / min in a rare gas atmosphere, and pyrolyze for 1.5 h to obtain a nitrogen-doped reduced graphene oxide / lead oxide composite material;
[0051] The prepared organic fiber AGM separator is applied to batteries.
[0052] The remaining raw materials and preparation process remain the same as in Example 1.
[0053] Comparative Example 1
[0054] Compared with Example 1, this comparative example differs in that aniline is not added, and the specific implementation steps of S2 are:
[0055] S2, 25g of graphene oxide, 15mL of deionized water and 15mL of anhydrous ethanol are uniformly dispersed by ultrasonication to obtain a mixed solution; 175mg of lead acetate powder is added to the mixed solution, ultrasonicated for 20min, stirred for 0.5h, hydrothermally reacted at 180°C for 24h, washed alternately with anhydrous ethanol and deionized water for 3 times, freeze-dried, heated to 450°C at a rate of 5°C / min in a rare gas atmosphere, and pyrolyzed for 1.5h to obtain a graphene oxide / lead oxide composite material;
[0056] The prepared organic fiber AGM separator is applied to batteries.
[0057] The remaining raw materials and preparation process remain the same as in Example 1.
[0058] Comparative Example 2
[0059] Compared with Example 1, this comparative example is different in that lead acetate is not added, and the specific implementation steps of S2 are:
[0060] S2. Ultrasonically disperse 25 g of graphene oxide, 15 mL of deionized water and 15 mL of anhydrous ethanol, slowly drop 0.3 mL of aniline, ultrasonicate for 20 min, stir for 0.5 h to obtain a mixed solution; hydrothermally react at 180 ° C for 24 h, wash with anhydrous ethanol and deionized water alternately for 3 times, freeze-dry, heat to 450 ° C at a rate of 5 ° C / min in a rare gas atmosphere, pyrolyze for 1.5 h, and obtain nitrogen-doped reduced graphene oxide;
[0061] The prepared organic fiber AGM separator is applied to batteries.
[0062] The remaining raw materials and preparation process remain the same as in Example 1.
[0063] Comparative Example 3
[0064] Compared with Example 1, this comparative example differs in that aniline and lead acetate are not added at the same time, and the specific implementation steps are as follows:
[0065] S1. High-alkali glass wool, medium-alkali glass fiber, and two-component polyester fiber are mixed in proportion to prepare a slurry, and then an AGM separator matrix is prepared according to an AGM separator preparation process;
[0066] S2. Evenly mix 30 mg of graphene oxide, 8 mg of boric acid, 5 g of lead oxide powder, 40 mg of barium sulfate, 20 mg of humic acid, 20 mg of sodium lignin sulfonate, 3 mg of short fibers, 8 mg of acetylene black, 1.5 mL of deionized water and 1 mL of 30% by mass dilute sulfuric acid to obtain a slurry. Apply the slurry on the AGM separator substrate, immerse it in a dilute sulfuric acid solution for 15 seconds, and cure it at an air humidity of 95% and room temperature of 60°C for 24 hours to obtain an organic fiber AGM separator.
[0067] The prepared organic fiber AGM separator is applied to batteries.
[0068] The remaining raw materials and preparation process remain the same as in Example 1.
[0069] Comparative Example 4
[0070] Compared with Example 1, this comparative example differs in that boric acid and aniline are not added at the same time, and the specific implementation steps are as follows:
[0071] S1. High-alkali glass wool, medium-alkali glass fiber, and two-component polyester fiber are mixed in proportion to prepare a slurry, and then an AGM separator matrix is prepared according to an AGM separator preparation process;
[0072] S2, 25g of graphene oxide, 15mL of deionized water and 15mL of anhydrous ethanol are uniformly dispersed by ultrasonication to obtain a mixed solution; 175mg of lead acetate powder is added to the mixed solution, ultrasonicated for 20min, stirred for 0.5h, hydrothermally reacted at 180°C for 24h, washed alternately with anhydrous ethanol and deionized water for 3 times, freeze-dried, heated to 450°C at a rate of 5°C / min in a rare gas atmosphere, and pyrolyzed for 1.5h to obtain a graphene oxide / lead oxide composite material;
[0073] S3. Evenly mix 30 mg of graphene oxide / lead oxide composite material, 5 g of lead oxide powder, 40 mg of barium sulfate, 20 mg of humic acid, 20 mg of sodium lignin sulfonate, 3 mg of short fibers, 8 mg of acetylene black, 1.5 mL of deionized water and 1 mL of 30% by mass dilute sulfuric acid to obtain a slurry containing the graphene oxide / lead oxide composite material. Apply the slurry on the AGM separator substrate, immerse it in a dilute sulfuric acid solution for 15 seconds, and cure it at an air humidity of 95% and room temperature of 60°C for 24 hours to obtain an organic fiber AGM separator.
[0074] The prepared organic fiber AGM separator is applied to batteries.
[0075] The remaining raw materials and preparation process remain the same as in Example 1.
[0076] Comparative Example 5
[0077] Compared with Example 1, this comparative example differs in that no nitrogen-doped reduced graphene oxide / lead oxide composite material is added, and the specific implementation steps are as follows:
[0078] S1. High-alkali glass wool, medium-alkali glass fiber, and two-component polyester fiber are mixed in proportion to prepare a slurry, and then an AGM separator matrix is prepared according to an AGM separator preparation process;
[0079] S3. Evenly mix 8 mg of boric acid, 5 g of lead oxide powder, 40 mg of barium sulfate, 20 mg of humic acid, 20 mg of sodium lignin sulfonate, 3 mg of short fibers, 8 mg of acetylene black, 1.5 mL of deionized water and 1 mL of 30% by mass dilute sulfuric acid to obtain a slurry. Apply the slurry on the AGM separator substrate, immerse it in a dilute sulfuric acid solution for 15 seconds, and cure it at an air humidity of 95% and room temperature of 60°C for 24 hours to obtain an organic fiber AGM separator.
[0080] The prepared organic fiber AGM separator is applied to batteries.
[0081] The remaining raw materials and preparation process remain the same as in Example 1.
[0082] Performance Test:
[0083] According to GB / T 28535-2018 "Lead-acid battery separator", the performance test of the organic fiber AGM separator prepared in Example 1 to Example 5 and Comparative Example 1 to Comparative Example 5 was performed;
[0084] The results are shown in Table 1:
[0085] Table 1
[0086]
[0087] It can be seen from the examples, comparative examples and the test data in Table 1 that the organic fiber AGM separator prepared by the present invention has a tensile strength of 0.96-1.03 KN / m, a tensile elongation of 4.25%-4.56%, a capillary acid absorption height of 105-113 mm / 5 min, and a weight loss due to acid immersion of 0.96% to 1.18%; the only difference between Examples 2-5 and Example 1 is that the raw material ratio is changed within a reasonable range. From the test results, organic fiber AGM separators with excellent performance can be obtained.
[0088] By comparing Comparative Examples 1-3 and Comparative Example 5 with Example 1, it is found that without the addition of aniline, due to the agglomeration of graphene oxide flakes, the binding tightness between the composite material and the negatively charged ions is reduced, resulting in a decrease in the performance of the separator. After adding lead acetate, not only the conductivity of graphene oxide can be improved, but also the resistance of the separator to dendrite thorns can be improved, which can be seen from the acid immersion weight loss data. At the same time, without adding aniline and lead acetate, and further without adding nitrogen-doped reduced graphene oxide / lead oxide composite materials, the performance of the material is further reduced, indicating the linkage synergistic effect between nitrogen doping and lead oxide. In addition, in combination with Comparative Example 4 and Comparative Example 1, it is also found that there is a combined effect between boric acid and nitrogen doping. Nitrogen doping can adjust the pore structure of graphene and increase the specific surface area. Boric acid can improve the binding force between the grid and the active substance, so that it can better combine with the active substance, thereby improving the battery cycle performance.
[0089] In summary, the present invention provides an organic fiber AGM separator and its application. The prepared organic fiber AGM separator has good resistance to dendrite punctures and can extend the service life of batteries when applied thereto, and has good application prospects.
[0090] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An organic fiber AGM separator, characterized in that: The invention comprises high-alkali glass wool, medium-alkali glass fiber, bicomponent polyester fiber and a slurry containing a nitrogen-doped reduced graphene oxide / lead oxide composite material; The nitrogen-doped reduced graphene oxide / lead oxide composite material is prepared by the following steps: Graphene oxide, deionized water and anhydrous ethanol are uniformly dispersed by ultrasonic method, aniline is slowly dropped into the mixture, and ultrasonic stirring is performed to obtain a mixed solution; lead acetate powder is added into the mixed solution, ultrasonic stirring is performed, hydrothermal reaction is performed, washing is performed, freeze drying is performed, and pyrolysis is performed in a rare gas atmosphere to obtain a nitrogen-doped reduced graphene oxide / lead oxide composite material.
2. The organic fiber AGM separator according to claim 1, characterized in that: The usage ratio of the graphene oxide, deionized water, anhydrous ethanol, aniline and lead acetate is (20-30) mg: (10-20) mL: (10-20) mL: (0.1-0.4) mL: (150-200) mg.
3. The organic fiber AGM separator according to claim 1, characterized in that: The ultrasonic time is 20-30 minutes; the stirring time is 0.5-1 hour.
4. The organic fiber AGM separator according to claim 1, characterized in that: The hydrothermal reaction is carried out at 180-200° C. for 20-24 hours.
5. The organic fiber AGM separator according to claim 1, characterized in that: The pyrolysis is performed by heating to 450-500° C. at a rate of 5-10° C. / min and pyrolyzing for 1-2 hours.
6. The organic fiber AGM separator according to claim 1, characterized in that: The method for preparing the organic fiber AGM separator comprises the following steps: S1. High-alkali glass wool, medium-alkali glass fiber, and two-component polyester fiber are mixed in proportion to prepare a slurry, and then an AGM separator matrix is prepared according to an AGM separator preparation process; S2. Evenly mix the nitrogen-doped reduced graphene oxide / lead oxide composite material, boric acid, lead oxide powder, barium sulfate, humic acid, sodium lignin sulfonate, short fibers, acetylene black, deionized water and dilute sulfuric acid to obtain a slurry containing the nitrogen-doped reduced graphene oxide / lead oxide composite material, apply the slurry on an AGM separator substrate, immerse it in a dilute sulfuric acid solution, and solidify it to obtain an organic fiber AGM separator.
7. The organic fiber AGM separator according to claim 6, characterized in that: The amount ratio of the nitrogen-doped reduced graphene oxide / lead oxide composite material, boric acid, lead oxide powder, barium sulfate, humic acid, sodium lignin sulfonate, short fibers, acetylene black, deionized water and dilute sulfuric acid is (20-40) mg: (5-10) mg: (4-6) g: (30-40) mg: (15-25) mg: (15-25) mg: (2-4) mg: (6-10) mg: (1-2) mL: (0.5-1) mL.
8. The organic fiber AGM separator according to claim 6, characterized in that: The mass fraction of the dilute sulfuric acid solution is 20% to 30%; the immersion time is 10-20s.
9. The organic fiber AGM separator according to claim 6, characterized in that: The curing conditions are as follows: air humidity of 90% to 95%, room temperature of 60-80° C., and curing for 20-24 hours.
10. Use of the organic fiber AGM separator according to any one of claims 1 to 9 in a battery.
Citation Information
Patent Citations
Porous aerogel AGM separator and preparation method thereof
CN104201319A
Preparation method of battery diaphragm resisting penetration of lead dendritic crystal
CN101702427A
Storage battery AGM separator, preparation method thereof and storage battery
CN103855346A
AGM diaphragm for lead-carbon battery and preparation method of AGM diaphragm
CN112615108A
Preparation method of reduced graphene oxide loaded lead oxide composite material for lead-carbon battery
CN114835159A
Cited By
Negative electrode additive of lead-acid battery as well as preparation method and application of negative electrode additive
CN121366896A
Lead-acid battery negative electrode additive, preparation method and application thereof
CN121366896B
Voltage response copolymer coated three-dimensional nitrogen-doped carbon material as well as preparation method and application thereof
CN121885932A